A note on classical damping matrices. - Luco, J. Enrique
An alternative damping matrix that leads to classical normal modes and that depends explicitly on a set of prescribed modal damping ratios is presented. The alternative damping matrix can be thought of as a factorized Caughey series that allows for a simple explicit solution for the coefficients of the series and thus avoids the need to solve a potentially ill conditioned system of algebraic equations. The relation between the proposed damping matrix and Rayleigh, Caughey and modal damping matrices is examined.
Keywords: Dynamics; Damping matrix; Classical modes